Avaliação da exposição ocupacional a Benzeno, Tolueno, Etilbenzeno e Xileno (BTEX) em serviços de pavimentação asfáltica com misturas usinadas a quente - CARVALHÊDO NETO, Miguel Melo (2018)
Professionals that work in asphalt paving activities are found in an extremely peculiar environment, exposed to unhealthy agents, like chemical substances, such as benzene, toluene, ethylbenzene and xylene (BTEX). There is an absence of specific national studies, with quantitative analysis, discussing the occupational exposure of the workers from the segment of asphalt paving to the mentioned substances. This research tries to evaluate the occupational exposure to BTEX experienced by the workers that actuate in the asphalt paving services that involves the application of hotmix batches. For that, the data were taken using passive samplers, model SKC 575- 002, fixed in the personal protective equipment of each worker, near the respiratory zone, during full working hours (8 hours). From the results obtained from the chemical analysis of the samplers, it can be stated that the existing concentrations in the workplaces are below the limits of quantification supported by the method and by the equipment used in the laboratory, but it can still be verified that the results obtained are at levels below the limits of occupational exposure. Thus, it is believed that the majority of workers can be exposed daily to the BTEX concentrations possibly present on the analyzed workplaces without suffering adverse health effects.